Earth - Luhr, James F.; Post, Jeffrey E. (London : Dorling Kindersley, 2013)
his is a breathtaking and inspirational exploration of planet Earth. From the fiery mass of the Earth's core to the tip of the highest ice-capped mountain, discover every aspect of our planet in awe-inspiring photographic detail with Earth. Visit 400 of the tallest, longest, widest, most significant and most unusual geographical features of planet Earth, from volcanoes, deserts and rivers to weather systems, rocks and minerals. Then take a look at the health of our planet and explore the interaction between people and the environment, from living in volcanic areas to deforestation, to understand the human impact on nature and how we can preserve our physical environment.
Previous edition published as Illustrated encyclopedia of the Earth. 2011.
Includes glossary and index.
Keywords: Earth sciences -- Encyclopedia; Earth (Planet) -- Encyclopedia